Analisis dan Redesign Aplikasi M-Paspor dengan Metode Design Thinking untuk Peningkatan Usability dan Pengalaman Pengguna - Mavish, Steven; Christanto, Henoch Juli; Sutresno, Stephen Aprius (Journal of Information System Research (JOSH), 2024)
The rapid advancement of information technology has significantly impacted various sectors, including public service. The Indonesian government's M-Paspor application, designed to streamline the passport application process, has faced several user experience challenges, such as complicated registration processes, inaccurate location selection, and difficulty in finding queue schedules. This study aims to analyze and redesign the M-Paspor application using the Design Thinking method, a user-centered approach involving empathy, problem definition, ideation, prototyping, and testing stages. Through a thorough literature review and usability analysis, we identified key issues affecting the application's performance based on four usability indicators: learnability, efficiency, errors, and satisfaction. The redesigned interface, developed using the Design Thinking framework, addresses these issues by improving clarity, navigation, and overall user experience. Our findings indicate that the redesigned M-Paspor application significantly enhances user satisfaction and efficiency, ultimately supporting the government's vision of effective and efficient e-governance. This study not only provides practical solutions for improving the M-Paspor application but also offers insights into the application of Design Thinking in public service technology design.